Ultrasound case of solid pseudopapillary tumor of the pancreas - L. E. Kozlova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The clinical case of a rare pancreatic tumor in a 8-year-old child with hypoglycemia (decrease in blood sugar to 1,5 mmol/l) is presented. A sonographic picture of the solid pseudopapillary tumor of the pancreas is shown. The capability of ultrasound investigation in differential diagnostics of small-size neoplasms at early stages is pointed out. The role of the Doppler's effect with color mapping in visualization of the pancreatic vascular pattern normality and at the verification of pancreatic pathological mass is described. Histological examination which identifies the cellular structure forms solid and pseudopapillary images.